A evasão nos cursos de graduação de química: uma experiência de sucesso feita no Instituto de Química da Universidade Federal do Rio de Janeiro para diminuir a evasão - Machado,Sérgio P. (2005)
The problem of the dropping out of the graduate chemistry courses is not new in the Brazilian University. What are the principal factors for this dropping out? Are there rules to measure this dropping out? In this work we present our experience in the Chemistry Institute of the Federal University of Rio de Janeiro to deal with this problem.